The best course available : a personal account of the secret U.S.-Japan Okinawa reversion negotiations - Wakaizumi, Kei, 1930-1996 (University of Hawai'i Press, 2002)
Challenging the silence of the official bureaucracies in Washington and Tokyo, Wakaizumi Kei reveals the truth behind the secret 1969 agreement that ensured the eventual reversion of Okinawa to Japanese jurisdiction in 1972. Revelation of this sec.